1985
DOI: 10.1139/v85-179
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of anhydrous and hydrated dimethylphosphinates of manganese(II). The crystal and molecular structure of poly-bis(μ-dimethylphosphinato)diaquomanganese(II)

Abstract: Can. J. Chem. 63, 1055 (1985. The dimethylphosphinate of manganese(ll), Mn[(CH3)zP02]2, and its dihydrate have been prepared and studied using magnetic susceptibility, differential scanning calorimetry, and electronic and vibrational spectroscopic methods. The dihydrate was obtained in crystalline form and a single crystal X-ray diffraction study revealed a polymeric structure.Crystals of~poly-bis(p-dimethylphosphinato)diaquomanganese(l1) are monoclinic, o = 20.722(3), b = 4.8652(2), c = 11.0689(14) A, P = 102… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…There is no signi®cant difference in the coordination distance between carboxyl and water O atoms. Most of the coordination bond distances in the present complex range from 2.1516 (14) to 2.216 (2) A Ê and are comparable to those reported previously, for example, 2.181 (1) in [Mn(H 2 O) 6 ] 2+ ÁZnBr 2À (Villella et al, 1986), 2.221 (6) in [Mn(HC 4 et al, 1995) and 2.247 (3) A Ê in [Mn II (Me 2 PO 2 ) 2 ]Á2H 2 O (Cicha et al, 1985). It is notable that the Mn1ÐO19 distance of 2.2922 (13) A Ê in the present Mn II complex is signi®cantly longer than the Mn II ÐO water distances reported so far for Mn II complexes and very close to the MnÐ O water distances of 2.319 (3) (Horwitz et al, 1995) and 2.287 (5) A Ê (Li et al, 2000) found in the axial direction of two Mn III complexes, both of which showed signi®cant Jahn±Teller distortion.…”
supporting
confidence: 89%
“…There is no signi®cant difference in the coordination distance between carboxyl and water O atoms. Most of the coordination bond distances in the present complex range from 2.1516 (14) to 2.216 (2) A Ê and are comparable to those reported previously, for example, 2.181 (1) in [Mn(H 2 O) 6 ] 2+ ÁZnBr 2À (Villella et al, 1986), 2.221 (6) in [Mn(HC 4 et al, 1995) and 2.247 (3) A Ê in [Mn II (Me 2 PO 2 ) 2 ]Á2H 2 O (Cicha et al, 1985). It is notable that the Mn1ÐO19 distance of 2.2922 (13) A Ê in the present Mn II complex is signi®cantly longer than the Mn II ÐO water distances reported so far for Mn II complexes and very close to the MnÐ O water distances of 2.319 (3) (Horwitz et al, 1995) and 2.287 (5) A Ê (Li et al, 2000) found in the axial direction of two Mn III complexes, both of which showed signi®cant Jahn±Teller distortion.…”
supporting
confidence: 89%
“…As discussed above, there is infrared evidence for unsymmetrical 0-P-0 units in this compound and this too may contribute to weakening the exchange. The aquo complex, 5, should exhibit both intrachain and interchain hydrogen bonding as has, in fact, been observed previously for the dimethylphosphinate analogue (8). This would be expected to give symmetrical 0-P-0 bridges in 5, a result supported by the infrared spectral studies described above.…”
Section: Temperature (K)supporting
confidence: 76%
“…Compounds of composition ML2(R2P02), in which metal ions are linked in chains by double phosphinate bridges forming square planar MO, chromophores with axially coordinated L groups are also known (8,9). The three atom 0-P-0 bridges in these polymeric materials have been shown to be capable of '~u t h o r to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The oxygen analogue of Me 2 PS 2 H, dimethylphosphinic acid Me 2 P(O)OH ( 1 ) reacts with metal cations to give “metal‐phosphinate‐bridged coordination polymers”, e.g. with Be II 5, Cr III 6, Mn II 7, Cu II 8. It coordinates to metal carbonyls (to yield e.g.…”
Section: Introductionmentioning
confidence: 99%